2016
DOI: 10.1063/1.4942113
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional nanoplates of Bi2Te3 and Bi2Se3 with reduced thermal stability

Abstract: Free-standing thin nanoplates of Bi2Te3 and Bi2Se3 were synthesized by solvothermal method. It was demonstrated that the thickness of the nanoplates can be controlled by introducing a controlled amount of polyvinylpyrrolidone (PVP) in the synthesis reaction. PVP bonds to the polar basal planes of hexagonal crystal structure of Bi2Te3 and Bi2Se3, and they suppress the growth (speed) of the hexagonal crystals in the c-axis direction. Highly anisotropic growth yielded the formation of 2-dimensional nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…With a band gap of 0.3 eV, Bi 2 Se 3 is the most important V-VI semiconductor [20][21][22][23]. Bi 2 Se 3 has an extensive application as thermoelectric and photoelectric materials near the room temperature [24,25]. Raman spectroscopy was an important tool to characterize the physical properties of various nanostructures, such as: 1T-TaS 2 [26], TiS 3 [27], MoS 2 [28], CoFe 2 O 4 [29], CuGaO 2 [30], Bi 3.25 La 0.75 Ti 3 O 12 [31], ZnSe [18,32], ZnO [33], etc.…”
Section: Introductionmentioning
confidence: 99%
“…With a band gap of 0.3 eV, Bi 2 Se 3 is the most important V-VI semiconductor [20][21][22][23]. Bi 2 Se 3 has an extensive application as thermoelectric and photoelectric materials near the room temperature [24,25]. Raman spectroscopy was an important tool to characterize the physical properties of various nanostructures, such as: 1T-TaS 2 [26], TiS 3 [27], MoS 2 [28], CoFe 2 O 4 [29], CuGaO 2 [30], Bi 3.25 La 0.75 Ti 3 O 12 [31], ZnSe [18,32], ZnO [33], etc.…”
Section: Introductionmentioning
confidence: 99%
“…5 Tuning the thickness of nanostructures may also permit control over transport phenomena. 6,7 Implementing these ideas is challenging, however, because most growth methods yield nanostructures in a great variety of sizes and shapes during the same process. This limits the ability to build devices to exact specifications and furthermore limits future scalability of geometrydependent devices.…”
Section: Introductionmentioning
confidence: 99%
“…7−9 Tuning the thickness of nanostructures may also permit control over transport phenomena. 10,11 Implementing these ideas is challenging, however, because most growth methods yield nanostructures in a great variety of sizes and shapes within the same process. This limits the ability to build devices to exact specifications and furthermore limits future scalability of geometry-dependent devices.…”
mentioning
confidence: 99%
“…This occurs with large surface-to-volume ratio, so nanostructures of Bi 2 Se 3 are of particular interest. , In addition, theoretical proposals have suggested that specific nanostructure geometries may be able to enhance the material properties of Bi 2 Se 3 in useful ways. For example, patterning an antidot lattice into Bi 2 Se 3 may greatly improve its thermoelectric figure of merit; , Bi 2 Se 3 wires could be used as efficient interconnects in integrated circuits; and creating Bi 2 Se 3 wires and rings, and possibly pairing them with a superconductor, may allow for control of Majorana fermions and other topological phenomena, potentially assisting in fault-tolerant quantum computing. Tuning the thickness of nanostructures may also permit control over transport phenomena. , Implementing these ideas is challenging, however, because most growth methods yield nanostructures in a great variety of sizes and shapes within the same process. This limits the ability to build devices to exact specifications and furthermore limits future scalability of geometry-dependent devices.…”
mentioning
confidence: 99%